Manganese incorporation in synthetic hercynite. (2nd January 2018) - Bromiley, G. D.; Gatta, G. D.; Stokes, T.
Abstract: Manganese incorporation in synthetic hercynite, and partitioning between hercynite and silicate melt synthesized at 1.0 GPa, 1250°C, and at an f O2 buffered by Fe–FeO, has been studied by X-ray absorption spectroscopy and single-crystal X-ray structure refinement. Spectra indicate the presence of both Mn 2+ and Mn 3+ (and possibly also Mn 4+ ) in synthetic hercynite and partitioning of Mn 2+ into the melt phase, and Mn 3+ into hercynite, respectively, under run conditions. X-ray refinement is consistent with partial disorder of Fe and Al across tetrahedral and octahedral sites. A higher than expected degree of Fe-Al disorder in the Mn-bearing hercynite can be explained by preferential incorporation of Mn 2+ onto the tetrahedral site, and indicates that Fe-Al disorder in pure, stoichiometric hercynite cannot necessarily be used to determine closure temperatures in natural spinel. However, partitioning of Mn 2+ and Mn 3+ between melt and hercynite suggests that Mn incorporation in hercynite could be used as a measure of f O2 conditions in magmas during spinel crystallization.